A new algorithm for improving the low contrast of computed tomography images using tuned brightness controlled single‐scale Retinex. Issue 2 (6th February 2015) - Al‐Ameen, Zohair; Sulong, Ghazali
Summary Contrast is a distinctive visual attribute that indicates the quality of an image. Computed Tomography (CT) images are often characterized as poor quality due to their low‐contrast nature. Although many innovative ideas have been proposed to overcome this problem, the outcomes, especially in terms of accuracy, visual quality and speed, are falling short and there remains considerable room for improvement. Therefore, an improved version of the single‐scale Retinex algorithm is proposed to enhance the contrast while preserving the standard brightness and natural appearance, with low implementation time and without accentuating the noise for CT images. The novelties of the proposed algorithm consist of tuning the standard single‐scale Retinex, adding a normalized‐ameliorated Sigmoid function and adapting some parameters to improve its enhancement ability. The proposed algorithm is tested with synthetically and naturally degraded low‐contrast CT images, and its performance is also verified with contemporary enhancement techniques using two prevalent quality evaluation metrics—SSIM and UIQI. The results obtained from intensive experiments exhibited significant improvement not only in enhancing the contrast but also in increasing the visual quality of the processed images. Finally, the proposed low‐complexity algorithm provided satisfactory results with no apparent errors and outperformed all the comparative methods. SCANNING 37:116–125, 2015. © 2015 Wiley Periodicals, Inc.